Investigation of the design and operating parameters of a portable mechanical arch breaker - Kozhevnikov V.A. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta)
An increase in the quality of unloading of hard-to-bulk materials from stationary and mobile bunker tanks can be achieved by using selective mechanical arch breakers. The configuration of the working bodies of these devices will ensure the stable production of a wide range of materials with different physical and mechanical properties from bunkers with different geometries. Using a theoretical tool that has found application in the research of metal and soil cutting processes, a theoretical description of the effect of the working bod¬ies of a portable arch breaker on the packed material in the hopper was given. Having studied the nature of the device’s operation directly in the cavity of the hopper outlet funnel (rotation of the working bodies with their one-time deviation at various stages of unloading the material), expressions were obtained to determine the operating loads and the power consumed. At the same time, in the obtained formulas, along with the physico-mechanical properties of the discharged materials, the design and operating parameters of the device were taken into account. Using the obtained expressions, the construction of theoretical dependencies is carried out, establishing the influence of several variable design-mode parameters (dimensions of working bodies, their feed, angular velocity) on the power consumed. The results of the conducted research can be used to optimize the structural and operating parameters of vaulting structures in the design of their laboratory and industrial samples.